Effect of Maceration Time on Color Intensity, Bioactive Compounds and Antioxidant Activity of Purple Corn Extract (Zea mays var. Black Aztec): Pengaruh Lama Maserasi Terhadap Intensitas Warna, Senyawa Bioaktif dan Aktivitas Antioksidan Ekstrak Jagung Ungu (Zea mays var. Black Aztec) - Mawarno, Binardo Adi Seno; Putri, Aldila Sagitaning; Fitriana, Ika (Universitas Slamet Riyadi Surakarta, 2024)
Purple corn is one of the corn varieties that is being developed by Indonesia as a form of food diversification. The purple color of corn is produced by the high presence of anthocyanins so it can provide health benefits such as antioxidant, anti-inflammatory, mutagenic, anti-cancer and anti-angiogenesis. To ensure that the bioactive components are not damaged, extraction is carried out in stages by applying the maceration method using a polar solvent with the correct ethanol content of 96%. Apart from using the appropriate solvent, the length of maceration time will determine the results of the extract obtained. This research aims to find out how long maceration affects the content of bioactive compounds found in purple corn. The research used a completely randomized design with one treatment, namely maceration times of 12, 24 and 48 hours. The tests carried out included color intensity, total phenol and anthocyanin content and antioxidant activity. The research findings explain that the length of maceration has a significant effect on color intensity, total phenols and antioxidant activity of purple corn extract. 2 hour maceration was the best treatment in extracting bioactive compounds, namely total phenols of 206.29 g/100 g, total anthocyanins of 0.19 g/100 g and antioxidant activity of 58.80%.